Alternative ways to correct poor glucose metabolism in patient with diabetes mellitus - Leonid Sevastyanov; Yermek Turgunov; Jean-Pierre Faure; Dmitriy Shestakov (National Scientific Medical Center, 2021)
There is an annual increase in the incidence of diabetes recorded worldwide. The existing measures of prevention and multimodal treatment of the disease have not yet brought the desired results. A promising field is bariatric (metabolic) operations used in obese patients, which also improve glucose metabolism in the case of concomitant diabetes mellitus of both types 1 and 2. At the same time, there is a certain contradiction and understatement regarding the mechanisms that lead to remission of diabetes mellitus, regardless of weight loss. One of the anatomical effects of bariatric procedures is the accelerated release of nutrients into the distal segment of the small intestine, which leads to stimulation of enteroendocrine cells and increased secretion of incretins (GLP-1, PYY, etc.). The experiment investigates these mechanisms by the operation of ileal transposition. Further study of the ileal transposition effects using different models of type 1 and type 2 diabetes, accompanied both with and without obesity, may contribute to a more detailed understanding of the triggering and supporting mechanisms of increasing glucose tolerance in the struggle against this disease.